Publisher Correction: Fundamental Social Motives Measured Across Forty-Two Cultures in Two Waves (Scientific Data, 2022 9 1 499 10.1038/S41597-022-01579-W) - Fernandez-Tapia, A (Nature Research, 2022)
In the html version of this article the affiliation details for Marco Antonio Correa Varella were incorrectly given as ‘eduLab21, Ayrton Senna Institute, São Paulo, 05423-040, Brazil’, but should have been ‘Department of Experimental Psychology, Institute of Psychology, University of São Paulo, São Paulo, 05508-030, Brazil’. This has now been corrected in the HTML version of the Article. The PDF version of the Article was correct at the time of publication. © The Author(s) 2022.